(untitled) (Global Journal of Management and Business Research, 2023)
Faced with the rivalry of the powers of the East and West for world domination, the way is opened to understand what are the interacting factors that determine the competitive advantages of both blocs in the race to achieve technological supremacy. The debate on how business strategies have been generated in East and West has been part of different interpretations, an analysis of the competitive advantages and disadvantages of both versions from the second post-war period and the different scenarios for which it has been necessary transited the cold war in international competition.